2014
DOI: 10.1021/ja501749b
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional DNA-Programmable Assembly of Nanoparticles at Liquid Interfaces

Abstract: DNA-driven assembly of nanoscale objects has emerged as a powerful platform for the creation of materials by design via self-assembly. Recent years have seen much progress in the experimental realization of this approach for three-dimensional systems. In contrast, two-dimensional (2D) programmable nanoparticle (NP) systems are not well explored, in part due to the difficulties in creating such systems. Here we demonstrate the use of charged liquid interfaces for the assembly and reorganization of 2D systems of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
82
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 47 publications
(76 reference statements)
1
82
0
Order By: Relevance
“…At the same time, assembling NPs into two-dimensional (2D) crystalline and noncrystalline structures have also been developed. In one approach, charged Langmuir monolayers have been used as templates that attract and crystallize capped nanoparticles from solutions [5][6][7]. In a different approach, it has been found that by manipulating salt concentrations in NPs suspensions, a Gibbs-like monolayer can be spontaneously formed and crystallized [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, assembling NPs into two-dimensional (2D) crystalline and noncrystalline structures have also been developed. In one approach, charged Langmuir monolayers have been used as templates that attract and crystallize capped nanoparticles from solutions [5][6][7]. In a different approach, it has been found that by manipulating salt concentrations in NPs suspensions, a Gibbs-like monolayer can be spontaneously formed and crystallized [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In a different approach, it has been found that by manipulating salt concentrations in NPs suspensions, a Gibbs-like monolayer can be spontaneously formed and crystallized [8][9][10]. It should be emphasized that for all these assemblies, 2D or 3D, salts play a decisive role in tweaking the charge of the DNA strands and facilitate specific 3D assembly of NPs or migration of NPs to the liquid interface [5][6][7][8][9][10]. In fact, a recent study suggests that the underlying mechanism that drives DNA-capped AuNPs to the surface and to crystallization has to do with the role of salt in tweaking the hydrophobic-hydrophilic character of the DNA-capped AuNPs [10].…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of LPFs has been intensively studied in the context of controlled self-assembly of homo-and block copolymers, 1−3 rheology of monolayers, 3−5 glass transition behavior of polymeric systems in 2D-or quasi 2D-confinement, 6,7 and structure formation in biological systems. 8,9 Monroy and coworkers made pioneering contributions to investigate the dynamic behavior of Langmuir films of flexible polymers prepared by subsequent material deposition to increase the surface density. 10−12 They showed that the air−water interface represents good solvent conditions for their chosen polymers [poly(vinyl-acetate) and poly(tert-butyl acrylate)].…”
Section: ■ Introductionmentioning
confidence: 99%
“…Experimentally, single NP membranes have been formed in a variety of ways, including using evaporation induced ordering [3,7] and DNA-programmable NPs [8]. In the case of evaporation induced ordering, NPs are driven by evaporation to the liquid/vapor interface [7].…”
mentioning
confidence: 99%